2015
DOI: 10.1111/ctr.12650
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pancreas transplantation: a review of the UK experience over a period of 10 yr

Abstract: Cold ischemia time <12 h and the use of depleting antibodies as induction immunosuppression have a positive effect on pancreas allograft survival. Other factors such as bladder-drained grafts and donor variables such as age, BMI, and DCD status did not attain significance in a multivariate analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…28 In the past, the PAK approach had a higher rate of early pancreas graft losses, often for technical reasons, and a lower long term pancreas graft survival rate than the SPK combination. 31 However, over the past decade, the greatest improvements in outcome have been made in the PAK category and the results of PAK no longer trail those of SPK. 20 The appropriate treatment option for transplant candidates with diabetes and chronic kidney disease depends on several factors, including the availability of a suitable living kidney donor, renal function at the time of referral to a transplant center, and expected waiting time for an SPK.…”
Section: Long Term Benefitsmentioning
confidence: 99%
“…28 In the past, the PAK approach had a higher rate of early pancreas graft losses, often for technical reasons, and a lower long term pancreas graft survival rate than the SPK combination. 31 However, over the past decade, the greatest improvements in outcome have been made in the PAK category and the results of PAK no longer trail those of SPK. 20 The appropriate treatment option for transplant candidates with diabetes and chronic kidney disease depends on several factors, including the availability of a suitable living kidney donor, renal function at the time of referral to a transplant center, and expected waiting time for an SPK.…”
Section: Long Term Benefitsmentioning
confidence: 99%
“…The prevalence of unexpected APR in grafts removed for duodenal leaks and peripancreatic collections may reflect the non‐depleting antibody induction regimen used in our unit. There is some evidence to suggest that depleting induction regimens lead to a lower rate of APR at three months but no clear evidence to suggest that they reduce graft loss . Of note, Al‐Adra et al also found APR in grafts explanted for duodenal leak, despite the use of depleting agents at induction .…”
Section: Discussionmentioning
confidence: 99%
“…The main causes of these complications and graft failure pointed by different authors are: surgical damage to the graft during procurement and vascular events mainly thrombosis [24,25]. Both may be related to the donor condition.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, attention was paid to the influence of the donor's age, BMI, alcohol use and other factors [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation